2020
DOI: 10.21203/rs.3.rs-17814/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of suprapatellar versus infrapatellar approaches of intramedullary nailing for distal tibia fractures

Abstract: Background: This study aimed to analyze and compare the clinical and functional outcomes of distal tibia fractures treated with intramedullary nailing (IMN) using the suprapatellar (SP) and infrapatellar (IP) surgical approaches.Methods: A retrospective analysis was performed in 63 patients with distal fractures that were treated with IMN between August 2014 and August 2018. A total of 27 and 36 patients underwent IMN using the SP and IP techniques, respectively. The surgical time, blood loss, closed reduction… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Chan et al 19 and Sun et al 23 found no significant differences between the 2 IMN groups. Lu et al 25 reported a significant difference with 3.7% malunion rate in the SP group and 25% malunion rate in the IP group ( P = 0.034). Although Metcalf et al reported a malunion rate of 6 of 107 in the SP group and 19 of 102 in the IP group, only 3 patients overall required revision surgery for malunion across both groups, 1 in the SP and 2 in the IP group.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Chan et al 19 and Sun et al 23 found no significant differences between the 2 IMN groups. Lu et al 25 reported a significant difference with 3.7% malunion rate in the SP group and 25% malunion rate in the IP group ( P = 0.034). Although Metcalf et al reported a malunion rate of 6 of 107 in the SP group and 19 of 102 in the IP group, only 3 patients overall required revision surgery for malunion across both groups, 1 in the SP and 2 in the IP group.…”
Section: Resultsmentioning
confidence: 95%
“…The most common PROM was the Lysholm Knee Score, which was reported by 7 studies. [19][20][21][22][23][24][25] Three studies used the Kujala Score 18,20,22 and 3 studies used a visual analogue scale for pain 19,21,23 to report patient outcomes. In total, 11 different PROMs were reported across all studies (see Table, Supplemental Digital Content 5, http://links.lww.com/JOT/B623).…”
Section: Promsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks very much for your interest in the article "Comparison of suprapatellar versus infrapatellar approaches of intramedullary nailing for distal tibia fractures" [1]. We agree with Dr. Lu's opinion that the description of the ideal starting point and Fig.…”
mentioning
confidence: 69%
“…29 Lu et al found less malalignment with the suprapatellar method in distal tibia fractures. 30 Therefore, we preferred the suprapatellar method.…”
Section: Discussionmentioning
confidence: 99%